Surface Modification of ZrO[2] -3Y[2] O[3] Ceramics with Continuous Ar{+} Ion Beams; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Kostenko V. Valeriya; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Ovchinnikov V. Vladimir; Gushchina N. Natalya; Makhinko F. Fedor (Ion Beam Processing of Materials. Oral Presentation, 2019)
Заглавие с экрана